Microrobot‐in‐glass for dynamic motion analysis and wider in vitro applications. (24th July 2019) - Salmon, Hugo; Couraud, Laurent; Roblin, Christophe; Hwang, Gilgueng
Abstract : Microrobots could become a key enabler in life science and medicine research as well as industrial applications. Although they provide high‐performance tools for a wide range of applications, their environment and particularly surface forces induce significant challenge for their control. This work introduces an originally integrated microrobot in a permanently sealed glass microfluidic chip. Compared to conventional polymer chips, the glass substrate offers a smooth, stable, and inert surface. It also avoids the typical contamination and fast degradation of organosilicon polymers. In this environment, they demonstrate high‐frequency hydrodynamics analysis and control. This strategy offers a high precision platform to study microrobot design and hydrodynamics as well as a transducer module for mapping surfaces and sensing interaction with physical environments.